2012
DOI: 10.1111/j.1528-1167.2012.03466.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal structural and functional brain connectivity in gray matter heterotopia

Abstract: Summary Purpose Periventricular nodular heterotopia (PNH) is a malformation of cortical development associated with epilepsy and dyslexia. Evidence suggests that heterotopic gray matter can be functional in brain malformations and that connectivity abnormalities may be important in these disorders. We hypothesized that nodular heterotopia develop abnormal connections and systematically investigated the structural and functional connectivity of heterotopia in patients with PNH. Methods Eleven subjects were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
81
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 35 publications
9
81
0
2
Order By: Relevance
“…For display purposes, an additional tractogram was also generated with 100,000 tracks for each participant using the exact same processing constraints. From a technical perspective, this whole brain tractography approach allowed us to avoid potential sources of error inherent in 'seed to target' region-of-interest-based tractography approaches where assessment of structural connectivity, and comparison to control subjects, is complicated by the absence in control subjects of structures corresponding to the ectopic clusters of neurons (27)(28)(29)(30)(31)(32). ( inferior-superior).…”
Section: Whole-brain Csd-based Tractography Mappingmentioning
confidence: 99%
“…For display purposes, an additional tractogram was also generated with 100,000 tracks for each participant using the exact same processing constraints. From a technical perspective, this whole brain tractography approach allowed us to avoid potential sources of error inherent in 'seed to target' region-of-interest-based tractography approaches where assessment of structural connectivity, and comparison to control subjects, is complicated by the absence in control subjects of structures corresponding to the ectopic clusters of neurons (27)(28)(29)(30)(31)(32). ( inferior-superior).…”
Section: Whole-brain Csd-based Tractography Mappingmentioning
confidence: 99%
“…A further elucidation of the networks associated with epilepsy, connecting deep or multiple foci with neocortical areas, would be of major interest and allow targeted network stimulation compared to non-targeted vertex stimulation in patients without a superficial EF. Pioneering work revealed abnormal structural and functional connectivity between deep heterotopic gray matter nodules and discrete regions of overlying cortex in patients with periventricular heterotopia [63]. A TMS-EEG study in these patients confirmed the presence of cortical hyperexcitability that was specifically linked to the cortical regions with aberrant connectivity to the heterotopic nodules [64].…”
Section: Stimulation Protocolmentioning
confidence: 91%
“…Furthermore, it is known that early disruption of cortical development is capable of reorganizing the brain and altering connectivity [12][13][14][15][16][17]54]. Therefore, it is likely that alterations in reciprocal corticothalamic/thalamocortical interactions as well as structural dysgenesis in other central auditory pathway structures (e.g., MGN, inferior colliculous, cochlear nucleus) may also be present.…”
Section: Introductionmentioning
confidence: 96%